2012
DOI: 10.1007/s10719-012-9455-5
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus parainfluenzae has a limited core lipopolysaccharide repertoire with no phase variation

Abstract: Cell surface lipopolysaccharide (LPS) is a well characterized virulence determinant for the human pathogen Haemophilus influenzae, so an investigation of LPS in the less pathogenic Haemophilus parainfluenzae could yield important insights. Using a panel of 18 commensal H. parainfluenzae isolates we demonstrate that the set of genes for inner core LPS biosynthesis largely resembles that of H. influenzae, with an additional heptosyltransferase I gene similar to waaC from Pasteurella multocida. Inner core LPS str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
2
1
Order By: Relevance
“…In agreement with the reported increase in bacterial translocation in cirrhotic patients, B. dentium , an opportunistic pathogen that mainly inhabits the oral cavity (Xu et al, 2012), and H. parainfluenzae residing primarily in the human upper respiratory tract (Young and Hood, 2013) increased during disease progression. Surprisingly, L. salivarius , and S. salivarius levels also increased during disease progression in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with the reported increase in bacterial translocation in cirrhotic patients, B. dentium , an opportunistic pathogen that mainly inhabits the oral cavity (Xu et al, 2012), and H. parainfluenzae residing primarily in the human upper respiratory tract (Young and Hood, 2013) increased during disease progression. Surprisingly, L. salivarius , and S. salivarius levels also increased during disease progression in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…Amongst the H. parainfluenzae strains tested we found no correlation between the type of OAg locus and the presence of particular H. influenzae -like outer core LPS biosynthesis genes that we had previously identified (Young and Hood, 2013) such as lpsB , losB1 and lic2C . This emphasises the high degree of genetic exchange that must occur in H. parainfluenzae , particularly in the genes required for OAg synthesis.…”
Section: Discussioncontrasting
confidence: 58%
“…We recently showed that in contrast to the closely related species Haemophilus influenzae , H. parainfluenzae does not phase vary the expression of its core LPS components by the tetranucleotide repeat mediated slippage of LPS biosynthesis genes (Young and Hood, 2013) and at least one strain expresses polymeric OAg (Vitiazeva et al, 2011). The latter observation concurs with the findings of Roberts and colleagues (1986) that some (8/25) H. parainfluenzae isolates give ladder-like LPS profiles using silver-stained SDS-PAGE, suggestive of molecules containing OAgs of different chain lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negative bacterium that normally resides within the human nasopharynx and periodontal spaces, where its carriage is usually without significant symptoms (19). This species is differentiated from the closely related Haemophilus influenzae by the lack of a strict requirement for hemin and differences in its surface glycolipid populations (20)(21)(22)(23). Notably, many of these surface factors lacking in H. parainfluenzae are those that we have previously shown to be important determinants of biofilm formation and maturation for H. influenzae (14,(24)(25)(26).…”
mentioning
confidence: 90%